If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3y + 2x + y = 0 Reorder the terms: 4x + 2x + 3y + y = 0 Combine like terms: 4x + 2x = 6x 6x + 3y + y = 0 Combine like terms: 3y + y = 4y 6x + 4y = 0 Solving 6x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 6x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 6x + 0 = 0 + -4y 6x = 0 + -4y Remove the zero: 6x = -4y Divide each side by '6'. x = -0.6666666667y Simplifying x = -0.6666666667y
| -7(t-2)-(t+1)=4 | | 5y^2-2y+4=0 | | (x+4)(x+4)+4=53 | | 4k+2-3k=18 | | 16+5w-10-(-3w)=10-12 | | 6x-8=6(x-4) | | x^2-17x+21=0 | | 7=(n/7)+9 | | 7k+5=-19 | | -4-3n=-13-6n | | 4k+2-3k=16 | | (2t-3)(2t+1)=5 | | 17-3d+8-4d=-9+13 | | 5-5d-6-5d= | | (x^2)-10x+16=0 | | n^2-23n=60 | | 3y^2+5y-8=0 | | 9(2x+8)=20-(x-5) | | 254=-7n-5(2-8n) | | 7+8b+3b-3= | | .57z+.66z=13 | | 6y^2+18y=0 | | .625x-10=-25 | | (2x+6)(x-4)=8 | | -20x+20=120 | | (2x+1)=4-3(2x+1) | | -5+3(x-5)=-31-10 | | 3(2x+5)=3x+23-x | | -y-8+6=-9+5y+1 | | 9=7(3-2x)-6(4-3x) | | X^2+-22x+120=0 | | -9+2x=15 |